BODY SHAMING DENGAN HARGA DIRI DAN MEKANISME KOPING REMAJA - Tutur Kardiatun (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2021)
BODY SHAMING DENGAN HARGA DIRI DAN MEKANISME KOPING REMAJA Fathul Khoir, Tutur Kardiatun, Cici Ultari, Parliani, Lidia Hastuti STIK Muhammadiyah Pontianak khoir@stikmuhptk.ac.id Abstract Background: adolescents have experienced body shaming which causes changes in self-esteem that stimulate adaptive or maladaptive coping mechanisms. Objective: to determine the relationship between body shaming and self-esteem with coping mechanisms adolescents at SMAN 2 Mempawah Hilir. Methods: descriptive research with cross sectional correlation approach, total sampling technique amounted to 50 students. The instrument uses the body Shaming Checklist sheet, Rosenberg Self-Esteem Scale, and Ways Of Coping. Results: There is no relationship between body shaming and adolescent self-esteem at SMAN 2 Mempawah Hilir (p = 0.596), and there is no relationship between body shaming and coping mechanisms in adolescents at SMAN 2 Mempawah Hilir (p = 0.456). Conclusion: majority of adolescents in SMAN 2 Mempawah Hilir have high or positive self-esteem with adaptive coping mechanisms. Some teenagers stated that body shaming is a criticism to improve themselves, divert body shaming in a spiritual way, such as prayer being given patience, and being ignorant. Keywords: Body Shaming, Self-Esteem, Coping Mechanism